2013
DOI: 10.26719/2013.19.9.775
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal characteristics in low birth weight and normal birth weight infants

Abstract: Low birth weight is a key determinant in the risk of morbidity and mortality in the neonatal period and during childhood. This unmatched case-control study in Hamadan, Islamic Republic of Iran, compared the characteristics of mothers of low-and normal-birth-weight infants. Maternal sociodemographic data, pregnancy history, anthropometric data and cord plasma zinc level were collected from 134 mothers of low-birth-weight infants and 134 mothers of normal infants at the time of delivery. Significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
2
9
1
1
Order By: Relevance
“…The association between low birth weight and prematurity is described in several studies (1,(3)(4)(5)(6)(7) , however there is one study that identifies that this association is inadequate. The authors (12) report that prematurity may be related to incorrect calculation of the probable date of delivery and to the increased occurrence of cesarean deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between low birth weight and prematurity is described in several studies (1,(3)(4)(5)(6)(7) , however there is one study that identifies that this association is inadequate. The authors (12) report that prematurity may be related to incorrect calculation of the probable date of delivery and to the increased occurrence of cesarean deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies (3)(4)(5)(6)(7)(8) point out smoking, low maternal level of education, younger maternal age, marital status, small weight gain during pregnancy, high blood pressure, infections of the genitourinary tract during pregnancy, twins, and fewer prenatal doctor check-ups as factors related to low birth weight. Consequently, LBW can be associated with a higher risk of infections, increased hospitalization, and a greater propensity to post-natal neuropsychological deficits (9) .…”
Section: Introductionmentioning
confidence: 99%
“…2 Bayi berat lahir rendah juga memiliki risiko tinggi untuk terjadinya penyakit kardiovaskuler, penyakit metabolik saat dewasa, dan keterlambatan pertumbuhan. 6 Oleh karena itu, penting untuk mengetahui faktor-faktor yang mempengaruhi BBLR seperti faktor ibu, faktor janin sendiri, dan faktor plasenta. 7 Semua faktor tersebut dapat dicegah dengan promosi kesehatan melalui kunjungan antenatal care (ANC).…”
Section: Pendahuluanunclassified
“…However few other studies contradicting this study and found a statistically significant association with LBW. 13,14 Majority 989 (96.02%) of mothers were Hindu. Nayak et al and Nagagorge et al also found Hindu as the major religion in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…Swarnalatha et al and many others showed consistent results with this study. 6,11,12,14,20,25 Here nicotine may be the agents most likely responsible for detrimental effects on intrauterine growth causing LBW.…”
Section: Discussionmentioning
confidence: 99%